Lado English Series : book 4 - Lado, Robert (New York : Regents Publishing Company, 1979)
Contiene:Comparing two states. Being late for work. Asking about people and place. Talking about programs on television. Trying to buy a very popular record. Problems with car repairs. Discussing a popular new singer. Confusion at the concert hall entrance. Asking for directions. Asking how to address an envelope.